2015
DOI: 10.1093/jnci/djv181
|View full text |Cite
|
Sign up to set email alerts
|

The Affordable Care Act and Expanded Insurance Eligibility Among Nonelderly Adult Cancer Survivors

Abstract: Under the ACA, many of the uninsured and a larger proportion of survivors facing financial hardship will be eligible for Medicaid or premium tax credits in the Marketplaces. ACA implementation will dramatically enhance insurance availability and is likely to reduce financial hardship for vulnerable cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 25 publications
0
57
0
Order By: Relevance
“…Earlier reports have shown that survivors of cancer who are without insurance may find it difficult to use medical care compared with survivors who have insurance, especially due to cost reasons [44,45], which may explain lower quality ratings from uninsured survivors. As our assessment was prior to the rollout of major Patient Protection and Affordable Care Act (ACA) provisions [46] that expands insurance eligibility, it is likely that some of the issues reported by survivors may be reduced as more obtain insurance [47]. At the same time, an increasing number of survivors will have access to public insurance via Medicaid expansion, meaning that future studies must determine how the ACA has impacted health care experiences of this population.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports have shown that survivors of cancer who are without insurance may find it difficult to use medical care compared with survivors who have insurance, especially due to cost reasons [44,45], which may explain lower quality ratings from uninsured survivors. As our assessment was prior to the rollout of major Patient Protection and Affordable Care Act (ACA) provisions [46] that expands insurance eligibility, it is likely that some of the issues reported by survivors may be reduced as more obtain insurance [47]. At the same time, an increasing number of survivors will have access to public insurance via Medicaid expansion, meaning that future studies must determine how the ACA has impacted health care experiences of this population.…”
Section: Discussionmentioning
confidence: 99%
“…18 In earlier assessments, uninsured survivors of AYA cancer reported skipping medical care more often than insured survivors, although dental care was not specifically investigated. 4 While the Affordable Care Act (ACA) is expected to enhance medical insurance availability for cancer survivors, 19 dental coverage is not part of the ACA's required essential health benefits, and Medicaid coverage of adult dental benefits varies state by state. 20 As a result, it is projected that the number of adults without dental benefits will only be reduced by a marginal 5% relative to 2010 figures.…”
Section: Introductionmentioning
confidence: 99%
“…There is no direct measure of eligibility for Medicaid or Marketplace premium subsidies in the NHIS or any other dataset, so it was necessary to generate an algorithm to assess likely eligibility, similar to prior studies evaluating insurance expansions. 7,28,29 As the algorithm used self-reported information on income and family structure, there may be errors in the eligibility assignments, biasing some of the estimated associations toward the null. Second, our sample size for adults with a cancer history may have limited statistical power when assessing coverage changes by eligibility category.…”
Section: Discussionmentioning
confidence: 99%
“…Before the enactment of the Affordable Care Act (ACA), an estimated 14.7% of cancer survivors aged below 65 years (1.4 million) lacked insurance. 7 This situation is largely due to loss of employment-based insurance and/or because of unavailable or unaffordable health insurance in the individual market due to history of cancer. 8,9 Most state Medicaid programs provided coverage only for adults with dependent children, low-income seniors, pregnant women, and the disabled, 10 and because most cancer survivors are not of child bearing age 11 relatively few qualified on this basis.…”
mentioning
confidence: 99%
See 1 more Smart Citation